2013
DOI: 10.1038/cddis.2013.427
|View full text |Cite
|
Sign up to set email alerts
|

miR-125b transcriptionally increased by Nrf2 inhibits AhR repressor, which protects kidney from cisplatin-induced injury

Abstract: MicroRNAs (miRNAs) have a role in the cellular defense mechanism. Nuclear factor erythroid-2-related factor 2 (Nrf2) increases antioxidant enzyme capacity. However, miRNA transcriptionally controlled by Nrf2 had been uncharacterized. Here we report that miR-125b is transactivated by Nrf2 and inhibits aryl hydrocarbon receptor (AhR) repressor (AhRR). Bioinformatic approaches enabled us to extract six candidate miRNAs. Of them, only miR-125b was increased in the kidney of mice treated with oltipraz. Nrf2 overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 59 publications
2
66
0
3
Order By: Relevance
“…Indeed, recent data showed that miRNAs that are downregulated in tumour cells with hyperactive NRF2 affect the metabolism of these cells 49 and that Nrf2-mediated upregulation of miR-125b suppresses expression of the aryl hydrocarbon receptor in the kidney 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, recent data showed that miRNAs that are downregulated in tumour cells with hyperactive NRF2 affect the metabolism of these cells 49 and that Nrf2-mediated upregulation of miR-125b suppresses expression of the aryl hydrocarbon receptor in the kidney 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Rather, it also controls expression of genes with other functions, such as regulation of cell proliferation and survival 13 . Chromatin immunoprecipitation followed by sequencing (ChIP-Seq) revealed that Nrf2 binds to promoters of genes encoding microRNAs (miRNAs, miRs) [13][14][15] , although the functional consequences remain largely unknown.…”
mentioning
confidence: 99%
“…miR-125b, which is directly regulated by Nrf2, has a controversial role in AD because it is upregulated in the brain of human AD patients and downregulated in APPswe/PSDE9 ADmouse models and in murine primary hippocampal neurons treated with soluble Ab peptide [124,125]. The authors suggest the neuroprotective role of this miR, at least in mice, reporting that miR-125b decreases the expression of the pro-apoptotic proteins Bak1 and p53, which are upregulated in some AD patients and in mouse primary cortical neurons.…”
Section: Cellular Physiologymentioning
confidence: 99%
“…There appears to be a role for both miR-29 and miR-125 family members in both HSC development and leukaemic stem cell maintenance [41]. Both miR-29 and miR-125 family members have been shown to be regulated by Nrf2 [39,42]. Indeed miR-125b may be a useful marker of AML disease progression in both adult and childhood AML patients [43,44] and probably stems from its role in the development of blood cells from HSCs [45].…”
Section: Nrf2mentioning
confidence: 99%